HANDICRAFTS MAKE DECORATIVE LAMPS FROM PLASTIC SPOONS AS A CREATIVITY EFFORT STKIP SINGKAWANG STUDENTS - Zulfahita Zulfahita; Nur Aisyah; Gita Gita; Nurul Nurul; Sri Novi (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2021)
Decorative lights are one of the room accessories that can beautify the house. In addition to making the atmosphere of the house more cheerful, decorative lights can also be a simple solution to decorating a room without having to pay a fortune. In the modern era like today, people are increasingly creative in creating home gardens so that they become more beautiful. In the midst of society, various kinds of lamps are circulating in demand. Here, the team created a new, unique and interesting innovation, namely a decorative lamp in the shape of a lotus flower, made from an arrangement of plastic spoons attached to a used jar. This necessary material is quite easy to find and we find a lot in the environment around us because it is often used as daily necessities. There are many important factors that must be considered in order to promote this business, including choosing the right location, a good marketing strategy and determining a price that is affordable for the community. The business analysis of the handicrafts of decorative lamps from used bottles and plastic spoons includes a SWOT analysis. The team did this strategy to sell handicrafts from used jars and plastic spoons by promoting it. The budget for making handicrafts from used jars and plastic spoons is IDR 10,220,000. the schedule for the implementation of this craft for 3 months.